2018
DOI: 10.31234/osf.io/9hgsk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iconicity in word learning and beyond: A critical review

Abstract: Interest in iconicity (the resemblance-based mapping between aspects of form and meaning) is in the midst of a resurgence, and a prominent focus in the field has been the possible role of iconicity in language learning. Here we critically review theory and empirical findings in this domain. We distinguish local learning enhancement (where the iconicity of certain lexical items influences the learning of those items) and general learning enhancement (where the iconicity of certain lexical items influences the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…This hypothesis generalises over all iconic forms, including onomatopoeia, and recent empirical evidence supports this (e.g. Perry, Perlman, & Lupyan, 2015; see Nielsen & Dingemanse, 2018). However, while the extant research presents a convincing argument towards the sound symbolism bootstrapping hypothesis in general, its perspective is limited; for a sufficient account we must consider the real-world learning and use of onomatopoeia if these forms are applicable to Imai and Kita's (2014) framework.…”
mentioning
confidence: 89%
“…This hypothesis generalises over all iconic forms, including onomatopoeia, and recent empirical evidence supports this (e.g. Perry, Perlman, & Lupyan, 2015; see Nielsen & Dingemanse, 2018). However, while the extant research presents a convincing argument towards the sound symbolism bootstrapping hypothesis in general, its perspective is limited; for a sufficient account we must consider the real-world learning and use of onomatopoeia if these forms are applicable to Imai and Kita's (2014) framework.…”
mentioning
confidence: 89%
“…The study of different aspects of the relation between word form and meaning has seen a huge increase over the last decades (see Dingemanse et al, 2015; Nielsen & Dingemanse, 2020; Sidhu & Pexman, 2018a, for reviews about this line of work). Contrary to the long-held position that natural languages need to be arbitrary to be effective communication tools (Hockett, 1960), numerous studies have shown the widespread presence of systematic relations between word form and meaning at the sub-morphemic level, painting a more similar picture to the original position held by de Saussure (1916) that, while being a cardinal organising principle of natural languages, arbitrariness is not absolute and form-meaning systematicity is present beyond morphology.…”
Section: Introductionmentioning
confidence: 99%
“…One cue we consider is iconicity, or the degree to which a word resembles its referent. For example, onomatopoeic words (e.g., choo choo, oink) provide referential transparency because they sound like what they reference; children typically acquire these words early (Frank, Braginsky, Yurovsky & Marchman, 2016; Laing, 2019; Motamedi et al., 2020; Nielsen & Dingemanse, 2020; Perry et al., 2015). While all languages contain some degree of iconicity, the visual nature of sign languages allows for more information to be communicated through iconic means (Perniss, Thompson & Vigliocco, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent evidence from sign language acquisition work suggests that deaf children acquire signs with particular iconic properties early (Caselli & Pyers, 2017; 2020; Ortega et al., 2017; Thompson et al., 2012). Additionally, theorists seem to agree that iconicity promotes the acquisition of iconic word forms (a so‐called “local learning effect;” Nielsen & Dingemanse, 2020). Within the visual modality, a proposed mechanism for this comes from one study on British Sign Language demonstrating that deaf parents tend to modify iconic signs in ways that highlight the shared features between the sign and its referent (Perniss, Lu, Morgan & Vigliocco, 2018).…”
Section: Introductionmentioning
confidence: 99%